A comparative study between Constraint-Induced Movement Therapy (CIMT) and Motor Imagery Technique with Rhythmic Auditory Stimulation (MI + RAS) for Motor Skill Development in Patients with Middle Cerebral Artery (MCA) Stroke - Gurjar, Bhavini; Lohar, Deepak; Khan, Jafar; Balala, Deepika; Menria, Shubham; Rai, Richa Hirendra; Pal, Renuka; Vyas, Rinshum; Kapoor, Shilpi; Sharma, Deepak (Journal of Neonatal Surgery, 2025)
Middle Cerebral Artery (MCA) strokes commonly result in motor deficits, hindering activities of daily living¹. This study compares the efficacy of Constraint-Induced Movement Therapy (CIMT)² and Motor Imagery (MI) combined with Rhythmic Auditory Stimulation (RAS)³ on motor skill development post-stroke. Forty patients diagnosed with MCA infarct were randomly assigned into two groups: Group A received CIMT, and Group B received MI + RAS. Treatment was administered for 16 weeks. Outcomes were measured using the STREAM and MMT scales. Results demonstrated significant improvement in both groups; however, CIMT showed greater gains in voluntary movement⁴, while MI + RAS showed better coordination in imagined and rhythmically cued tasks⁵. The study suggests tailored therapy depending on patient responsiveness.